Characteristics of changes in the structural components of the mucosa and rat laryngeal cartilage at the end of the third week of experimental opioid exposure - Ivasivka, K. P.; Paltov, E. V.; Masna, Z. Z. (Journal of Education, Health and Sport, 2021)
In our work we aimed to study the pathomorphological manifestations among the structural components of the laryngeal mucosa and cartilage in the early stages of the experimental opioid effect. This goal was achieved through the use of histological techniques to visualize the structural components of the laryngeal mucosa and cartilage. Histological sections with a thickness of 5 - 7 mm were made. Histological specimens were prepared according to conventional methods using the dye hematoxylin, eosin, azan according to the method of Heidenhain, PAS-reaction according to Mc-Manus and Alcian blue according to Steedman. Microscopic examinations and photographing of the preparations were performed using an MBI-1 microscope and a Nicon D 3100 digital camera. At the microstructural level after 21 days in rats there was an increase in dyscirculatory changes, which were most pronounced in the vessels of the lamina propria of the laryngeal mucosa. The epithelial layer of the epiglottis was inhomogeneously thickened, especially on the pharyngeal surface. Small polymorphonuclear infiltrates were found in the laryngeal mucosa of the epiglottis. The vessels of the laryngeal ventricular mucosa of the larynx were dilated and filled with erythrocytes. The development of perivascular edema was registered. In the areas of transudate accumulation, the main substance of the laryngeal mucosa of the larynx was enlightened. Necrotic changes developed in the epitheliocytes of the laryngeal ventricle. Eosinophilic mass accumulated on the surface of the ventricular mucosa. The results of the study in the future will form a pathomorphological base that can be used for comparative characterization of the dynamics of growth of pathomorphological changes in the structural components of the laryngeal mucosa and cartilage in the early stages and compare these changes with pathomorphological manifestations in the late stages of experimental opioid exposure.